The Effect of Differentiated Instruction and Digital Literacy on the Readiness of Pre-service Teachers at Makassar State University with Self-Efficacy as a Mediating Variable - SUHARTINI; Rahmatullah; Najamuddin (SOSIOEDUKASI, 2025)
This study aims to analyze the effect of differentiated learning and digital literacy on the readiness of pre-service teachers at Makassar State University with self-efficacy as a mediating variable. The background of this study is based on the importance of mastering pedagogical competencies, digital technology, and professional self-confidence in meeting the demands of 21st-century learning. The study used a quantitative approach with Partial Least Squares–Structural Equation Modeling (PLS-SEM) analysis and involved 280 pre-service PPG students as respondents. The results showed that differentiated learning had a positive and significant effect on teacher readiness, as did digital literacy, which was proven to improve prospective teachers' ability to utilize learning technology. Self-efficacy also has a direct influence on teacher readiness and is influenced by both variables. Furthermore, the mediation test results show that self-efficacy significantly mediates the influence of differentiated learning and digital literacy on pre-service teacher readiness. These findings confirm that the professional readiness of prospective teachers does not only depend on pedagogical skills and digital literacy, but also on their level of self-confidence, which enables them to optimize learning strategies and technology effectively. This study concludes that strengthening self-efficacy can reinforce the role of differentiated learning